Serum sclerostin levels in rheumatoid arthritis and correlation with disease activity and bone mineral density - Urmila Dhakad; Rasmi Ranjan Sahoo; Akhil Pawan Goel; Sourav Pradhan; Ragini Srivastava; Siddharth Kumar Das (Indian Journal of Rheumatology)
Background: This study aims to assess serum sclerostin, an inhibitor of the Wnt/β-catenin signaling pathway, in rheumatoid arthritis (RA) and its correlation with disease activity and bone mineral density (BMD). Methods: RA patients (>18 years) fulfilling the ACR/EULAR (2010) criteria for RA were included. Postmenopausal women, those with other autoimmune diseases, secondary causes of osteoporosis, severe vitamin D deficiency, chronic liver disease, chronic kidney disease stage 3 and above, and those patients on anticonvulsants were excluded. Rheumatoid factor, anticitrullinated protein antibody, 25-OH Vitamin D estimation, plain radiographs of hands, and BMD measurement by dual-energy X-ray absorpiometry were done in patients. Disease activity was assessed by clinical disease activity index (CDAI). Serum sclerostin levels in RA patients and controls (age and sex matched) were measured by commercial enzyme-linked immunosorbent assay (ELISA) and the relationship of sclerostin with low BMD, ESR, CDAI, and erosion were explored. Results: The mean age of patients (n = 47) was 32.7 ± 6.8 years and mean disease duration was 4.2 ± 2 years. All patients were women, mean body mass index was 22.38±4.4 and mean vitamin D level was 27.9±16.4 ng/ml. 25.5% of RA patients had low BMD at least one site (Z-score: −2 or less). Serum sclerostin was significantly higher in patients compared to controls (8422 ± 3655 pg/ml vs. 6479 ± 1510 pg/ml, P = 0.002). Serum sclerostin levels did not correlate significantly with ESR (r = −0.31 and P = 0.048), CDAI (r = −0.11 and P = 0.45), BMD at lumbar spine (L1–L4, r = 0.14, and P = 0.35), femur neck (r = 0.06 and P = 0.67), and wrist (r = 0.12 and P = 0.41). Conclusion: Serum sclerostin levels were elevated in RA patients but did not correlate with disease activity and BMD.